An empirical study of the use of neuroscience in sentencing in New South Wales, Australia - Alimardani, Armin (Frontiers in Psychology, 2023)
While neuroscience has been used in Australian courts for the past 40 years, no systematic empirical study has been conducted into how neuroscientific evidence is used in courts. This study provides a systematic review on how neuroscientific evidence is considered in sentencing decisions of New South Wales criminal courts. A comprehensive and systematic search was conducted on three databases. From this search, 331 relevant sentencing decisions before 2016 that discussed neuroscientific evidence were examined. The findings of this study suggest that neuroscientific evidence appeared to contribute to sentencing decisions in less than half of the cases examined; and in the majority of these, it supported a more lenient sentence.